SISTEM KEWARISAN DALAM ISLAM PERSFEKTIF KEADILAN GENDER - Zulfan Efendi Hasibuan (Yayasan Baitul Hikmah al-Zain, 2024)
As a legal principle, Islam does not distinguish between genders. The increasing demands between women and men affect the legal system of society. So there is a very important change in the definition of law. This amendment is a requirement for women to have equal rights in the family. Differences in the calculation of hereditary distributions lead to differences in interpretation of the injustice of gender differences. Because this concept does not give a sense of entitlement to women who have several roles. This study uses a literature research research method, namely. methods of collecting, reading and recording library materials, as well as activities related to the processing of research materials. A person receives a greater inheritance, which means the magnitude of his or her responsibilities and role in the family. And no, this is not a form of oppression and injustice against women in terms of inheritance, in fact the Qur'an makes it clear that women also have the same rights in terms of war.